Three-Term Presidency: The Perspectives from Democracy and Maslahah Mursalah - Rizqi, Retanisa (As-Siyasi: Journal of Constitutional Law, 2024)
The presidential and vice-presidential elections on February 14, 2024, raised a significant issue: the debate over the three-term presidency, which sparked considerable controversy among the public. This study examines the concept of the three-term presidency from the perspectives of democracy and Maslahah Mursalah. This research employs normative legal research with a descriptive approach, utilizing qualitative methods. The study focuses on Article 7 of the 1945 Constitution, analyzing it from the viewpoint of democracy. Furthermore, the Islamic legal analysis is analyzed with Maslahah Mursalah. The findings of this study indicate that the limitation of the presidential term to two periods, as stipulated in Article 7 of the 1945 Constitution, is beneficial and does not threaten democracy. Furthermore, from the perspective of Maslahah Mursalah, the analysis of benefits (maslahah) and harms (mafsadah) suggests that extending the presidential term to three periods would result in greater harm than benefit. Thereby, rendering it inadvisable and potentially threatening to public welfare.